Usage Effects on the Cognitive Routinization of Chinese Resultative Verbs - Wang, Ben Pin-Yun (Research in Language, 2012)
The present study adopts a corpus-oriented usage-based approach to the grammar of Chinese resultative verbs. Zooming in on a specific class of V-kai constructions, this paper aims to elucidate the effect of frequency in actual usage events on shaping the linguistic representations of resultative verbs. Specifically, it will be argued that while high token frequency results in more lexicalized V-kai complex verbs, high type frequency gives rise to more schematized V-kai constructions. The routinized patterns pertinent to V-kai resultative verbs varying in their extent of specificity and generality accordingly serve as a representative illustration of the continuum between lexicon and grammar that characterizes a usage-based conception of language.